Adam Naruszewicz’s Translation of Tacitus - Bober-Jankowska, Magdalena (Colloquia Litteraria, 2019)
In 1772-1773 Adam Naruszewicz, one of most outstanding representatives of Polish Enlightenment, wrote the first complete translation of all Tacit’s works. The study is devoted to Naruszewicz’s translation work on the texts of Roman historian. Adam Naruszewicz translated them onto Polish and published them in three volume, entitled „All works of Kaj Kornelius Tacit. Translation of Adam Stanisław Naruszewicz S.J.”. The study presents a translation workshop of the bishop’s of Smoleńsk, with a special consideration of the description of the mechanisms governing the preparation of scientific commentaries. Previous research concerning the bishop’s commentary work did not at all raise the issue of authorship, claiming that the commentaries were written by Naruszewicz. The Smoleńsk bishop’s commentary work was assessed very highly by the critics. However, the outcome in comparative research of Naruszewicz’s translation and the bases of translations presented in this study allowed to formulate new statements according to which scientofic commentaries in Tacit’s first Polish translation betray a far-reaching, multidimensional dependence on the source of translation, which allows to set and prove the thesis that the bishop was their author.